Pola Komunikasi Terapis dalam Menggunakan Metode ABA (Applied Behavior Analysis) di Yayasan Our Dream Indonesia - Misbach Hussudur; Dedeh Fardiah (Bandung Conference Series: Public Relations, 2024)
Abstract. Communication patterns are a form or series of processes of sending information from communicator to communicant. Meanwhile, autism is a disorder or abnormality that attacks brain and nerve function. This allows sufferers to experience shortcomings and limitations in various ways, one of which is the process of communicating and interacting with the surrounding environment. Communication patterns can be said to be a method that can be used by therapists in the process of providing therapy and learning, so that the information provided can be received well and run effectively. This research aims to find out how therapist communication patterns use the Applied Behavior Analysis (ABA) method that occurs at the Our Dream Indonesia foundation. The type of research carried out was qualitative with a case study method. The data collection stages carried out by the researcher used an interview process, observation, and were also assisted by additional data obtained by the author such as files, journals and others. After that, the results of the conversation analyzed by the researcher were processed to the stage of drawing conclusions. The sources interviewed in this research were three senior therapists and one psychologist at the Our Dream Indonesia foundation. The results of the research show that the communication pattern used by the therapist is a primary communication pattern which is demonstrated by the use of verbal and non-verbal. Apart from that, in the process of communication and interaction there are of course supporting factors such as the child's condition, the child's mood, and also the closeness that exists between the therapist and the autistic child. Barriers from internal and external factors also influence the communication process between therapists and autistic children. Abstrak. Pola komunikasi merupakan sebuah bentuk atau rangkaian proses pengiriman informasi dari komunikator ke komunikan. Sementara, autisme merupakan sebuah gangguan atau kelainan yang menyerang pada fungsi otak dan saraf. Hal ini memungkinkan pengidap mengalami kekurangan dan keterbatasan dalam berbagai hal, salah satunya adalah proses komunikasi dan berinteraksi dengan lingkungan sekitar. Pola komunikasi bisa dikatakan sebagai sebuah cara yang bisa digunakan oleh terapis dalam proses pemberian terapi dan pembelajaran, agar informasi yang diberikan dapat diterima dengan baik dan berjalan efektif. Penelitian ini bertujuan untuk mengetahui bagaimana pola komunikasi terapis dalam menggunakan metode Applied Behavior Analysis (ABA) yang terjadi di yayasan Our Dream Indonesia. Jenis penelitian yang dilakukan adalah kualitatif dengan metode studi kasus. Tahapan pengumpulan data yang dilakukan oleh peneliti menggunakan proses wawancara, observasi, dan juga dibantu oleh data tambahan yang didapat oleh penulis seperti berkas, jurnal dan lainnya. Setelah itu, hasil pembicaraan yang dianalisis oleh peneliti diolah hingga pada tahap penarikan kesimpulan. Narasumber yang diwawancarai pada penelitian ini yaitu sebanyak tiga orang terapis senior dan satu orang psikolog di yayasan Our Dream Indonesia. Hasil penelitian menunjukkan Pola komunikasi yang digunakan oleh terapis adalah pola komunikasi primer yang ditunjukan dengan penggunaan bahasa verbal dan nonverbal. faktor pendukung seperti kondisi anak,mood anak, dan juga kedekatan yang terjalin antara terapis dan anak autis. Hambatan dari faktor internal dan eksternal juga mempengaruhi proses berkomunikasi antara terapis dan anak autis.